KETAMINE IN PAIN MANAGEMENT AND PSYCHIATRIC TREATMENT: CURRENT KNOWLEDGE AND IMPLICATIONS FOR CLINICAL PRACTICE - Zofia Bogiel; Antonina Machała; Aleksandra Bielak; Aleksandra Foryś; Monika Kałwak; Daria Kuczwalska; Maria Spychalska; Daria Trocka (International Journal of Innovative Technologies in Social Science, 2026)
Research objectives: Ketamine, a derivative of phencyclidine, is a dissociative anesthetic that is used not only in anesthesia but also in analgesic and psychiatric settings such as perioperative and chronic pain, opioid-induced hyperalgesia and treatment-resistant depression management. With the general population’s prevalence of 2-40% for chronic pain and similar lifetime values for depression, ketamine deserves attention as an alternative to commonly used treatments. This research describes the use of subanesthetic ( 0,3 mg/kg to 0,5 mg/kg) ketamine doses in pain management and psychiatric settings, discusses its safety concerning psychomimetic and physical adverse effects and dependence risk, and suggests future research directions. Methods: Review of literature including peer-reviewed studies, meta-analyses, randomized controlled trials, clinical guidelines, focusing on ketamine pharmacokinetics, anesthetic and antidepressant effects, safety and clinical applications. Findings: Ketamine produces satisfactory short-term pain alleviation and rapid antidepressant action. It is part of multimodal anesthesia protocols as an adjuvant to other local anesthetics, prolonging their effects, and is a safe alternative for analgesia in opioid-tolerant patients. It has many routes of administration, which is used in patients with difficult intravenous access in emergencies. It provides a beneficial respiratory effect, alleviates chronic neuropathic and cancer pain, offers rapid response in acute depression including suicidal ideation, prevents post-operative depression risk and supports neuroplasticity. Conclusions: Ketamine is a promising drug in anesthesiology and psychiatry, but its long-term safety is not yet determined. Future research should focus on identifying biomarkers that determine treatment response, optimizing dosage, and discovering safer derivatives.